Agricultural diversification and smallholders in South Asia - Joshi, P. K.; Gulati, Ashok, 1954-; Cummings, Ralph Waldo; Academic Foundation (New Delhi, India) (New Delhi : Academic Foundation, 2007)
Contributed articles at two workshops.
Includes statistical tables.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects -- South Asia -- Congresses; Agricultural diversification -- South Asia -- Congresses; Small business -- South Asia -- Congresses; Agriculture -- Economic aspects -- South Asia -- Statistics; Agricultural diversification -- South Asia -- Statistics; Small business -- South Asia -- Statistics